Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi Melalui Terapi Spiritual Emotional Freedom Technique (SEFT) dan Akupresur Titik Taichong - Roni Saputra; Budhi Mulyadi; Mahathir Mahathir (Universitas Batanghari Jambi, 2020)
Hypertension is a disease that often occurs in the elderly and will have an impact on the quality and quantity of life of the elderly, so it needs early treatment. SEFT therapy and taichong point acupressure are complementary therapies that can lower blood pressure in the elderly. The design in this research is descriptive statistics. The sample was taken by purposive sampling and obtained 30 respondents who were divided into 15 respondents each in the SEFT group and the taichong point acupressure group. Data were collected using observation sheets and analyzed univariately. The results of the research in the SEFT group showed that the pre-test systolic blood pressure was 164.00, the diastole was 94.67 and the post-test systolic blood pressure was 149.67, the diastole was 90.00. Whereas in the taichong point acupressure group, the pre-test systolic blood pressure was 153.33, the diastole was 93.33 and the systolic blood pressure post-test was 142.67, the diastole was 88.67. SEFT therapy and taichong point acupressure can be an alternative in reducing blood pressure in the elderly.